Enhanced Transmission Performance Using Digital Back Propagation and Extended Kalman Filtering for Dispersion Unmanaged Links - Pakala, Lalitha; Schmauß, Bernhard (Signal Processing in Photonics and Communications, 2016)
The transmission performance of extended Kalman filtering (EKF) significantly outperforms one-step-per-span optimized digital back propagation (DBP). At the expense of few DBP steps deployed prior to EKF yields further enhanced non-linear tolerance.
lhft_intern.bib::Pakala2016d